PENGARUH PENGETAHUAN, SIKAP, DAN KETERSEDIAAN ALAT PELINDUNG DIRI (APD) TERHADAP KEPATUHAN DALAM MENGGUNAKAN APD DI UNIT COATING PT. PURA BARUTAMA KUDUS - Prasetyo, Eko (Universitas Muhammadiyah Semarang, 2015)
Use of Personal Protective Equipment (PPE) including environmental factors because APD is one tool to protect the workers themselves in order to reduce the risk of workplace accidents. Based on the first survey that the writer doing to 20 workes in subdivision product in Coating Unit in PT. Pura Barutama Kudus about the discipline in using APD, this result of observation in the field get 17 (85%) workes didn’t use APD in time to work and 3 (15%) workes using APD. The design of the research is use project planning Regresi Logistic survey for study dynamic influence between the factors risk (knowledge, attitude, reward and punishment, and availibility APD) with effect (discipline using APD) with approach way observation or collecting data in one time (point time approach), the sample that use is about 65 workes in subdivision product. The result of statistic test with Regresi Logistic Test, the influence between knowledge variabel with discipline using APD get p-value = 0,000 ; attitude with discipline using APD get p-value = 0,000 ; and availability APD with discipline using APD get p-value = 0,009. There is influence between independent variable is knowledge, attitude, reward and punishment, and also availability APD with dependent variable is discipline using APD ti workes in subdivision product in Coating unit in PT. Pura Barutama Kudus.Keywords: Personal Protective Equipment (PPE), Discipline PPE, Knowledge, Attitude, Avalibility APD.